2021
DOI: 10.12688/wellcomeopenres.16701.1
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the duration of seropositivity of human seasonal coronaviruses using seroprevalence studies

Abstract: Background: The duration of immunity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is still uncertain, but it is of key clinical and epidemiological importance. Seasonal human coronaviruses (HCoV) have been circulating for longer and, therefore, may offer insights into the long-term dynamics of reinfection for such viruses. Methods: Combining historical seroprevalence data from five studies covering the four circulating HCoVs with an age-structured reverse catalytic model, we estimated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…We estimated that anti-S IgG antibodies had a half-life of 1.47–3.15 years in children, and 2.57–5.33 years in adults, consistent with previous reports for other coronaviruses [8,22–27]. Based on these data, we assumed prior estimates for seroreversion rates of 0.3–1.4 year −1 in children and 0.2–0.7 year −1 in adults, consistent with estimates of 0.9–3.8 year −1 published by Rees et al [ 7 ]. However, after we fit serocatalytic models to the cross-sectional SeroPed data, our posterior median estimates for the half-life of seroreversion were in the range 13–33 years in children and 7–68 years in adults, substantially longer than prior estimates.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We estimated that anti-S IgG antibodies had a half-life of 1.47–3.15 years in children, and 2.57–5.33 years in adults, consistent with previous reports for other coronaviruses [8,22–27]. Based on these data, we assumed prior estimates for seroreversion rates of 0.3–1.4 year −1 in children and 0.2–0.7 year −1 in adults, consistent with estimates of 0.9–3.8 year −1 published by Rees et al [ 7 ]. However, after we fit serocatalytic models to the cross-sectional SeroPed data, our posterior median estimates for the half-life of seroreversion were in the range 13–33 years in children and 7–68 years in adults, substantially longer than prior estimates.…”
Section: Discussionsupporting
confidence: 78%
“…Serology, based on the detection of antibodies induced by previous infections, has been frequently used to measure population-level HCoV transmission [ 7 ]. As with SARS-CoV-2, the most immunodominant antigens for the 4 HCoVs are spike (S) and nucleocapsid (N).…”
mentioning
confidence: 99%
“…Since previous work has shown that the annual risk of infection and the seroreversion rate often cannot be reliably estimated from cross-sectional seroprevalence data simultaneously due to identifiability issues [ 18 ], we used our empirical estimate for the rate of seroreversion in Model 2. For both models, we initially considered infection risk to be constant across age and time, then, to reflect apparent differences in the rate of change of seroprevalence in children and adults in our data, we repeated model fitting whilst allowing the risk to be different in adults than in children as implemented previously [ 27 , 28 ]. We varied the age at which risk of infection changed between 12 and 36 years to conservatively cover the transition into adulthood.…”
Section: Methodsmentioning
confidence: 99%
“…Bayesian estimation was applied throughout the following analyses [ 9 ]. For selection of the priors in the first part, we referred to 2 previous reports: using the best fitted MSIS model, Nyiro et al [ 19 ] estimated the FoI for 0- to 1-year-olds and for 1- to 12-year-olds as 0.78 (95% confidence interval [CI], .65–.97) and 1.69 (95% CI, 1.27–2.04) per year, respectively, and Nakajo and Nishiura [ 15 ] estimated the FoI for primary and secondary infection as 0.12 per month (95% CI, .07–.18) and 0.05 per month (95% CI, 0.04–0.06), respectively.…”
Section: Methodsmentioning
confidence: 99%